Pengaruh Platform Facebook Terhadap Promosi Haji dan Umrah di Era Digital Pada Tahun 2024 PT. Light Water Tour - Hafizoh; Naura Ghaida Syifa; Said Agil Hasan; Abdul Hafiz (Teewan Journal Solutions, 2024)
This research aims to investigate the influence of the Facebook platform on the promotion of Hajj and Umrah in the digital era in 2024, especially at PT. Light Water Tour. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews and analysis of the company's Facebook content. The findings show that effective use of Facebook can increase the visibility and attractiveness of Hajj and Umrah promotions, create greater consumer engagement and expand audience reach. The practical implication of this research is the importance of integrating social media platforms such as Facebook Tiktok etc. in marketing strategies for the religious travel industry in today's digital era.